Performance appraisal system in higher education institutions : a case study of APAR system in IIUM - Jamilah binti Rabingan (Kulliyyah of Education, International Islamic University Malaysia, 2014)
This research will concentrate on examining the views of administrative officers in IIUM on the practicality of performance appraisal system which is known as Annual Performance Appraisal (APAR) system. Besides, this study attempts to explore the benefits and usefulness of appraisal system in improving employee's job performance as well as to trace the problems and dilemma encountered during its implementation process. This study employed semi-structured interview in collecting data which focusing on two level interviews. The first level interview was conducted on four administrative officers while the second level interview was conducted on two supervisors. The findings revealed that participants had positive views and met their expectations about the current performance appraisal, including the importance, objectives and methods of this system. It was also found that they are allowed to participate in the process of developing the standards of performance appraisal. Meanwhile, the data revealed that participants get a lot of benefits and very useful in improving their job performance as it provides opportunities for career development and improvement. Besides, it also showed that participants had been satisfied with the rating marks given by their supervisors pertaining to their overall job performance. Last but not least, the data also identified several problems and dilemma faced by administrative officers including time constraint, irrelevant job scope and supervisor which eventually became the barrier in improving job performance. Finally, the study concluded by proposing several recommendations for future research.